A genetic algorithm approach to VLSI macro cell non-slicing floorplans using binary tree - Hasliza, A. Rahim@Samsuddin; Ab Rahman, A. A H; Andaljayalakshmi, G.; R. Badlishah, Ahmad; Wan Nur Suryani Firuz, Wan Ariffin (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org